"A Superior Kind of Working Woman": The Contested Meaning of Vocational Education for Girls in Progressive Era Chicago. (July 2021) - Oram, Ruby
Abstract: Progressive Era school officials transformed public education in American cities by teaching male students trades like foundry, carpentry, and mechanics in classrooms outfitted like factories. Historians have demonstrated how this "vocational education movement" was championed by male administrators and business leaders anxious to train the next generation of expert tradesmen. But women also hoped vocational education could prepare female students for industrial careers. In the early twentieth century, members of the National Women's Trade Union League demanded that public schools open trade programs to female students and teach future working women the history of capitalism and the philosophy of collective bargaining. Their ambitious goals were tempered by some middle-class reformers and club women who argued vocational programs should also prepare female students for homemaking and motherhood. This article uses Chicago as a case study to explore how Progressive Era women competed and collaborated to reform vocational education for girls, and how female students responded to new school programs designed to prepare them for work both in and outside the home.